Clean code applied : building a Java web application with software craftmanship (Clean code video series., 2017)
Even bad code can function. But if code isn’t clean, it can bring a development organization to its knees. Robert C. Martin and Micah Martin reveal the disciplines, techniques, tools, and practices that separate software craftsmen from mere "9-to-5" programmers.--Includes text from resource description page.